Nitric Oxide Mediates Molybdenum-Induced Antioxidant Defense in Wheat under Drought Stress - Wu, Songwei; Hu, Chengxiao; Tan, Qiling; Xu, Shoujun; Sun, Xuecheng (Frontiers in Plant Science, 2017)
Molybdenum (Mo) has been reported to alleviate drought stress by enhancing antioxidant defense in plants, but the underlying mechanism remains unclear. Here, we hypothesized that Mo mediates nitric oxide (NO)-induced antioxidant defense through Mo-enzymes, particularly by nitrate reductase (NR) in wheat under drought stress. The 30-day-old wheat seedlings cultivated in –Mo (0 µM Mo) and +Mo (1 µM Mo) Hoagland solutions were detached and then pretreated with Mo-enzyme inhibitors, NO scavengers, NO donors or their combinations according to demands of complementary experiment under 10% polyethylene glycol 6000 (PEG)-stimulated drought stress (PSD). Mo supplementation increased the activities and transcripts of antioxidant enzymes, decreased H2O2 and MDA contents, and elevated NO production, implying that Mo-induced antioxidant defense may be related to NO signal. Complementary experiment showed that NO production was induced by Mo, while suppressed by Mo-enzyme inhibitors and NO scavengers, but restored by NO donors, suggesting that Mo-induced increase of NO production may be due to the regulation by Mo-enzymes. Further experiment indicated that the increased activities and transcripts of antioxidant enzymes induced by Mo were suppressed by Mo-enzyme inhibitors and NO scavengers, and NO donors could eliminate their suppressing effects. Moreover, Mo application increased NR activity and inhibitors of Mo-enzymes inhibited NR activity in wheat leaves under PSD, suggesting that NR might involve in the regulation of Mo-induced NO production. These results clearly indicate that NO mediates Mo-induced antioxidant defense at least partially through the regulation of NR.